A naphthalimide-based fluorescent probe for the highly sensitive and selective detection of nerve agent mimic DCP in solution and vapor phase. (17th June 2020) - Xu, Hui; Zhang, Han; Zhao, Lei; Peng, Cheng; Liu, Guohua; Cheng, Tanyu
Abstract : The fluorescent probe for DCP displays excellent selectivity and sensitivity with a low detection limit of 5.5 nM in DMF. Abstract : Although human beings enjoy a relatively peaceful atmosphere, chemical terrorist attacks are still a public safety emergency, and the ability to rapidly and precisely detect chemical warfare agents (CWAs) presents a major challenge. In this study, we have developed a simple fluorescent probe based on naphthalimide that displays high selectivity and sensitivity for the nerve agent mimic diethyl chlorophosphate (DCP) in DMF solution. This probe, which is weakly fluorescent because of the PET character of the piperazine moiety, displays significant green emission in the presence of DCP. Based on the fluorescence calibration curve, the detection limit of this DCP probe was measured to be as low as 5.5 nM. Futhermore, the probe solution or filter paper can be used to selectively and sensitively detect DCP vapor, which shows the potential of its practical application.